2017
DOI: 10.1370/afm.2031
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychological and Educational Interventions to Prevent Depression in Primary Care: A Systematic Review and Meta-Analysis

Abstract: PURPOSE Although evidence exists for the efficacy of psychosocial interventions to prevent the onset of depression, little is known about its prevention in primary care. We aimed to evaluate the effectiveness of psychological and educational interventions to prevent depression in primary care. METHODSWe conducted a systematic review and meta-analysis of relevant randomized controlled trials (RCTs) examining the effect of psychological and educational interventions to prevent depression in nondepressed primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Different studies have shown that depression is preventable [ 5 7 ]. In addition, prevention of depression is relatively good value for money [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have shown that depression is preventable [ 5 7 ]. In addition, prevention of depression is relatively good value for money [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prevention of depression is relatively good value for money [ 8 ]. However, the effect sizes of prevention are small, and most of the interventions are implemented by mental health specialists [ 5 7 ]. This jeopardizes its translation to primary health care centres, which may be a good setting for implementing preventive interventions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Information and communication technologies (ICT) can be employed for spreading these preventive interventions, as well as their implementation in settings such as school, primary care and the workplace. Currently, there is evidence of the effectiveness of ICT-based depression prevention programs (11) in schools (12) and primary care (13). Nevertheless, there is a lack of evidence regarding their effectiveness in the workplace.…”
mentioning
confidence: 99%
“…18 Examining the effectiveness of psychological or educational primary care interventions to prevent depression, a systematic review and meta-analysis of clinical trials finds a small effect. 19 Finally, in contrast, or perhaps in complement to the high-tech interventions in this issue, an essay by Edgoose explores the possibilities for generating hope through a low-tech means: the face-to-face encounter.…”
Section: Mental Healthmentioning
confidence: 99%